Pemanfaatan limbah tempurung kelapa untuk pembuatan asap cair menggunakan metode pirolisis: Utilization of coconut shell waste to make liquid smoke using the pyrolysis method - Evahelda, Evahelda; Astuti, Rufti Puji; Aini, Sitti Nurul; Nurhadini (AGROMIX, 2023)
Introduction: In the Bangka Belitung Islands Province, the use of coconuts is currently limited to the fruit only. Whether consumed fresh (young coconut water and young fruit flesh), or processed as food (grated coconut and coconut milk), the coconut shell and husk have not been utilized optimally. Efforts to optimize coconut shells can be used as raw material for making liquid smoke. The aim of this research is to describe the process of making liquid smoke from coconut shell waste by utilizing the resulting shell waste and classifying liquid smoke based on its color. Methods: The process of making liquid smoke in this research is by utilizing solid coconut shell waste from coconut milk presses around campus, then processing it into liquid smoke, using a pyrolysis equipment (Grant from the Ministry of Research, Technology and Higher Education in 2009) at a temperature of 300Â°C for 8 hours . Results: The results of the research show that the liquid smoke produced is blackish brown in color with an L value, smaller than grades 2 and 1, while the a and b values are greater than grades 2 and 1, so it can be classified into grade 3. Conclusion: Liquid smoke Grade 3 cannot be used for food preservatives, because it still contains a lot of tar which is carcinogenic. The use of liquid smoke can only be used as a coagulant and odor remover in rubber processing because liquid smoke has anti-fungal and anti-bacterial properties, pesticides, wood and bamboo preservatives to make it resistant to termites.